Protective effects of Tibetan kefir in mice with ochratoxin A-induced cecal injury. (August 2022) - Du, Gengan; Chang, Shuaidan; Guo, Qi; Yan, Xiaohai; Chen, Hong; Shi, Kehan; Yuan, Yahong; Yue, Tianli
Graphical abstract: Highlights: OTA exposure induced cecum injury and gut microbiota dysbiosis. TK protect the gut barrier, and suppress oxidative stress and inflammation. TK inhibited the activation of the TLR4-NF-κB signaling pathway induced by OTA. TK balance gut microbiota composition and SCFAs production. Abstract: Ochratoxin A (OTA) is reported to cause intestinal damage following ingestion of contaminated foods. Tibetan kefir (TK) is a fermented dairy product that possesses antioxidant, anti-inflammatory, and gut microbiota-regulating properties. However, it is not clear if TK can alleviate OTA-associated intestinal toxicity. Here, we investigated whether TK can prevent OTA-induced intestinal barrier disruption in mice. To this end, OTA-fed mice were treated with sterile water (control) or TK by oral gavage once daily, for 3 weeks. The histological changes of ceca, the expression of tight junction proteins and mucins, and the levels of oxidative stress, inflammatory response, and gut microbiota were then assessed. Results revealed that treatment with TK reversed OTA-driven histopathological changes in the ceca, and was associated with increased cecal mucin levels. TK administration to OTA-treated mice significantly elevated the expression levels of tight junction proteins (claudin-1, zonula occludens-1, and occludin). Additionally, TK supplementation suppressed OTA-induced oxidative stress and reduced inflammation via the NF-κB signaling pathway in the ceca. Moreover, TK supplementation depleted harmful bacteria (e.g., Turicibacter and Desulfovibrio ), while supporting short-chain fatty acids (SCFAs)-producing bacteria (e.g., Lachnospiraceae, Blautia, and Ruminococcus ), which maintained the SCFAs levels. Taken together, our findings indicate that TK may emerge as a viable dietary strategy to prevent intestinal toxicity-based injuries.